2018
DOI: 10.1016/j.eats.2018.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Method of Arthroscopically Confirming Femoral Button Deployment for Knee Anterior Cruciate Ligament Graft Suspensory Cortical Fixation

Abstract: Accurate deployment of the femoral button on the lateral aspect of the lateral femoral condyle when using a suspensory fixation device for anterior cruciate ligament reconstruction is ideal. Direct visualization would be the most appropriate method of visualization in the lateral gutter. A previously described technique is performed with the knee in flexion. In this position, maneuverability of the arthroscope in the lateral gutter may be difficult in small knees because of tight lateral structures. We describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Perumal et al modified this technique with the knee in full extension in order to relax the lateral soft tissue and obtain better visualization of the lateral gutter [8]. In our experience, we found advantages in performing button exploration with the knee in full extension allowing better visualization of the button deployment and better removal of the soft tissue around the button.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Perumal et al modified this technique with the knee in full extension in order to relax the lateral soft tissue and obtain better visualization of the lateral gutter [8]. In our experience, we found advantages in performing button exploration with the knee in full extension allowing better visualization of the button deployment and better removal of the soft tissue around the button.…”
Section: Discussionmentioning
confidence: 65%
“…However, there is a radiation exposition for the patients, increased time in the operating room, and risk of field contamination if performed intra-operatively. Arthroscopic exploration of the lateral gutter to ensure femoral button deployment is recently described with the aim to reduce soft tissue interposition and reduce the need for radiographic control [7][8][9][10][11]. Although the surgical technique has been reported by many authors, the real benefits of this procedure has not been well demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Arthroscopic direct visualization of the button deployment is a more effective method. Several studies have reported that the proper position was achieved through an arthroscopic view of the lateral gutter of the knee or an iliotibial band portal 4 , 8 , 11 , 16 in ACLR. It was reported that the femoral button placed with direct visualization was more likely to have an optimal position directly on the femoral cortex compared with indirect methods (0% vs 8.8%; P = .046).…”
Section: Discussionmentioning
confidence: 99%
“…Direct arthroscopic visualization, marking the femoral tunnel length on the graft, intraoperative fluoroscopy, and direct visualization of the button through a direct lateral incision have all been described. 2 , 8 - 10 , 12 Direct arthroscopic visualization is achieved by insertion of the arthroscope through the anteromedial portal, facilitating an unobstructed view of the femoral tunnel as the button is pulled through and out the smaller cortical hole, and by visualization of the button as it exits the tunnel to then be flipped horizontally. Balldin et al 1 described the use of intraoperative fluoroscopy to verify that the button is seated against the lateral femoral cortex.…”
mentioning
confidence: 99%